Benthic cyanobacterial mat formation during severe coral bleaching at Lizard Island: The mediating role of water currents. (November 2022) - Tebbett, Sterling B.; Streit, Robert P.; Morais, Juliano; Schlaefer, Jodie A.; Swan, Sam; Bellwood, David R.
Abstract: Cyanobacterial mats are increasingly recognised as a symptom of coral reef change. However, the spatial distribution of cyanobacterial mats during coral bleaching has received limited attention. We explored cyanobacterial mat distribution during a bleaching event at Lizard Island and considered hydrodynamics as a potential modifier. During bleaching cyanobacterial mats covered up to 34% of the benthos at a transect scale, while some quadrats (1 m 2 ) were covered almost entirely (97.5%). The spatial distribution of cyanobacterial mats was limited to areas with slower water currents. Coral cover declined by 44% overall, although cyanobacterial mats were not spatially coupled to the magnitude of coral loss. Overall, the marked increase in cyanobacterial mat cover was an ephemeral spike, not a sustained change, with cover returning to 0.4% within 6 months. Cyanobacterial mats clearly represent dynamic space holders on coral reefs, with a marked capacity to rapidly exploit change, if conditions are right. Graphical abstract: Image 1 Highlights: An ephemeral bloom of cyanobacterial mats occurred during severe coral bleaching. Cyanobacterial mats covered up to 34% of the benthos but were spatially patchy. Cyanobacterial mat formation was not spatially linked to the extent of coral loss. High cyanobacterial mat cover was associated with slower water currents. Cyanobacteria represent dynamic space holders which can exploit coral reef change.